2020
DOI: 10.3390/su12041514
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Risk Delay in Construction Projects Using a Hybrid Artificial Intelligence Model

Abstract: Project delays are the major problems tackled by the construction sector owing to the associated complexity and uncertainty in the construction activities. Artificial Intelligence (AI) models have evidenced their capacity to solve dynamic, uncertain and complex tasks. The aim of this current study is to develop a hybrid artificial intelligence model called integrative Random Forest classifier with Genetic Algorithm optimization (RF-GA) for delay problem prediction. At first, related sources and factors of dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 52 publications
1
47
0
Order By: Relevance
“…These countries have experienced rapid development; therefore, there is no doubt that the building industry provides a crucial role in providing basic living [4]. This field's success indicators are measured by quality, cost, and time of construction projects [5]. The construction industry has experienced significant changes in meeting the developing countries' commercial requirements and goals [6].…”
Section: Introductionmentioning
confidence: 99%
“…These countries have experienced rapid development; therefore, there is no doubt that the building industry provides a crucial role in providing basic living [4]. This field's success indicators are measured by quality, cost, and time of construction projects [5]. The construction industry has experienced significant changes in meeting the developing countries' commercial requirements and goals [6].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the delay categories can be based on the resources used such as delays due to materials, equipment or through functional areas such as contracts, procurement management, etc. [14][15][16][17][18][19][20][21]. The review showed 7 prominent factors reported by more than 50% of the authors.…”
Section: Literature Reviewmentioning
confidence: 94%
“…If the implementation of a project exceeds the assumed deadline, the method shows irregularities, i.e., it indicates that the project was implemented in accordance with the plan. These difficulties have influenced the development of formulas and methods for more reliable forecasting of the total cost and deadline of projects, e.g., by introducing hybrid methodology that is based on construction packages and the logical analysis of time [41], by introducing hybrid artificial intelligence [42], or by considering the impact of unplanned time and cost deviations on the financial liquidity of a construction project [38].…”
Section: Literature Reviewmentioning
confidence: 99%